2013
DOI: 10.1242/dev.099184
|View full text |Cite
|
Sign up to set email alerts
|

The nuage mediates retrotransposon silencing in mouse primordial ovarian follicles

Abstract: SUMMARYMobilization of endogenous retrotransposons can destabilize the genome, an imminent danger during epigenetic reprogramming of cells in the germline. The P-element-induced wimpy testis (PIWI)-interacting RNA (piRNA) pathway is known to silence retrotransposons in the mouse testes. Several piRNA pathway components localize to the unique, germline structure known as the nuage. In this study, we surveyed mouse ovaries and found, for the first time, transient appearance of nuage-like structures in oocytes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 39 publications
1
69
0
1
Order By: Relevance
“…Intriguingly, several piRNA pathway proteins such as DDX4, MILI, TDRD9 and GASZ are expressed in mouse oocytes [91]. Furthermore, in null mutants for each of these proteins, LINE1 is upregulated in the primordial follicles of the ovary, similar to observations in male germ cells [91].…”
Section: A Role For Line1 In Fetal Oocyte Attritionmentioning
confidence: 89%
“…Intriguingly, several piRNA pathway proteins such as DDX4, MILI, TDRD9 and GASZ are expressed in mouse oocytes [91]. Furthermore, in null mutants for each of these proteins, LINE1 is upregulated in the primordial follicles of the ovary, similar to observations in male germ cells [91].…”
Section: A Role For Line1 In Fetal Oocyte Attritionmentioning
confidence: 89%
“…For example, more than one quarter of mouse (27.7%) and human (28.5%) Refseqs possess at least one retrotransposon in their 3’ UTRs. In zebrafish, Xenopus and mouse oocytes, Piwi proteins and piRNAs are mainly found in the cytoplasm, and they are involved in the suppression of retrotransposons (Houwing et al, 2007; Lau et al, 2009; Lim et al, 2013; Watanabe et al, 2008). These observations suggest that retrotransposons are suppressed by piRNA pathway post-transcriptionally in vertebrate oocytes.…”
Section: Mrna Regulation By Pirnas Derived From Transposonsmentioning
confidence: 99%
“…In mouse oocytes, insertion of transposon sequences confers instability to reporter mRNAs (Watanabe et al, 2006). A recent study revealed that some transposon-driven mRNAs harboring transposon sequences in their 5’ UTRs are upregulated in Mvh, Mili, and Gasz mutant oocytes (Lim et al, 2013). These observations suggest that these transposon-driven mRNAs are directly regulated by piRNAs through the transposon sequences in their 5’ UTRs.…”
Section: Mrna Regulation By Pirnas Derived From Transposonsmentioning
confidence: 99%
See 2 more Smart Citations